Study on the impacts of leaders' positive psychological capital and personality on followers - Zhang, Jieying (2009)
This study examines the impacts of leaders’ positive psychological capital and personality on organizational commitment, employee engagement, job satisfaction and life satisfaction of employees in the service industry of Singapore. Survey responses were collected from 194 employees from the retail, banking and hotel sectors. Results from linear regression indicate that leaders’ positive psychological capital and self-efficacy and conscientiousness have significant impacts on all the subordinate outcomes measured. Leaders’ trust was found to have a positive and significant impact on only subordinate’s general health. Implications and limitations are discussed.